Customization in minimally invasive orthognathic surgery - Jonathas Daniel Paggi Claus; Matheus Spinella Almeida; Devid Zille (Elsevier, 2021)
Patient-specific implants are currently a new reality to orthographic surgery. Among other advantages offered by this technology, the following stand out: Splintless surgery; Maxillary three-dimensional repositioning with no vertical reference needed and minimal mandible proximal segment rotation. Most of the available patient-specific systems requires extended incisions to accommodate the cutting and drilling guides and the patient-specific fixation plates, with wide dissection. "Minimally invasive surgery" is already a well-known concept in several medical specialties, which has also recently been adopted in orthognathic surgery with its potential benefits. The authors of this article describe the customization of fixation devices under the concept of minimally invasive approaches.